Abundant and Rare Microbial Biospheres Respond Differently to Environmental and Spatial Factors in Tibetan Hot Springs - Zhang, Yanmin; Wu, Geng; Jiang, Hongchen; Yang, Jian; She, Weiyu; Khan, Inayat; Li, Wenjun (Frontiers in Microbiology, 2018)
Little is known about the distribution and ecological functions of abundant, middle and rare biospheres and their correlations with environmental factors in hot springs. Here, we explored the microbial community composition of total, abundant, and rare biospheres in 66 Tibetan hot springs (pairwise geographic distance 0-610 km, temperature 32-86oC, pH 3.0-9.5, and salinity 0.13-1.32 g/L) with the use of Illumina MiSeq high-throughput sequencing. The results showed that the abundant sub-communities were mainly composed of Chloroflexi, Proteobacteria, Deinococcus-Thermus, Aquificae, Bacteroidetes and Firmicutes. In contrast, the rare sub-communities mainly consisted of most newly proposed or candidate phyla of Dictyoglomi, Hydrogenedentes, Atribacteria, Hadesarchaea, Aminicenantes, Microgenomates, Calescamantes, Omnitrophica, Altiarchaeales and Chlamydiae. However, the abundant and rare sub-communities shared some common phyla (e.g., Crenarchaeota, Bathyarchaeota, Chlorobi), which were composed of different OTUs. The abundant, middle, and rare sub-communities were mainly influenced by different environmental variables, which could be ascribed to the fact that they may have different growth and activity and thus respond differently to environmental variables. Spatial factors showed more contribution to shaping of the middle and rare communities than to abundant sub-community, suggesting that the abundant taxa were more easily dispersed than their rare counterparts among hot springs. Microbial ecological function prediction revealed that the middle and rare sub-communities may play more important roles in organic degradation than their abundant counterparts in hot springs. Moreover, microbial ecological functions of the abundant and rare sub-communities responded differently to the measured environmental factors, suggesting they may occupy different ecological niches in hot springs. Collectively, this study provides a better understanding on the microbial community structure and potential ecological functions of the abundant and rare biospheres in hot spring ecosystems. The identified rare taxa provide new opportunities of ecological, taxonomic and genomic discoveries in Tibetan hot springs.